2021
DOI: 10.1007/978-3-030-68288-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic Evaluation of COVID-19 Chatbots

Abstract: Chatbots have been adopted in the health domain and their number grew during the current COVID-19 pandemic. As a new kind of interface, chatbots combine visual elements with natural conversation. While conversational capabilities of chatbots improve, little attention has been given to the evaluation of the user experience and chatbot usability. This paper presents the results of a heuristic review of 24 COVID-19 chatbots on different channels (webchat vs messengers), for diverse topics (symptom-checker vs FAQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…This affected the user's control and freedom. This finding is similar to the studies by (Höhn and Bongard-Blanchy, 2020;Jeddi et al, 2020), where it was found that applications without backward and forward navigation buttons make it difficult for users to navigate between the pages. Most of the menu titles of the G-MoMo applications are not uniformly aligned.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This affected the user's control and freedom. This finding is similar to the studies by (Höhn and Bongard-Blanchy, 2020;Jeddi et al, 2020), where it was found that applications without backward and forward navigation buttons make it difficult for users to navigate between the pages. Most of the menu titles of the G-MoMo applications are not uniformly aligned.…”
Section: Discussionsupporting
confidence: 91%
“…This affected the applications' error diagnosis and recovery. It was well confirmed by other studies (Caro-Alvaro et al, 2018;Höhn and Bongard-Blanchy, 2020), who observed that the applications do not indicate the error occurrence and the error was not explained in plain language. (Eliseo et al, 2017) recommended that error messages be displayed clearly.…”
Section: Discussionsupporting
confidence: 83%
“…The ongoing COVID-19 pandemic has further driven the rapid uptake and deployment of chatbots [ 6 ], many making use of commercial chatbot development platforms such as IBM’s Watson Assistant, Google Dialogflow, Yellow Messenger, and Turn.io to develop custom chatbots to help combat the disease. In the face of the burden placed upon health care systems by the pandemic, chatbots have enabled the automation of services toward addressing the need for physical distancing and helped disseminate information and relieve the pressure on medical services by public health systems around the globe [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Backpropagation [15] is used in this approach to learn Gradient decent, a is the learning rate which a = 0.01, where ∆w i refers to weights (y i -y i ) is the evaluation of error as specified in (4).…”
Section: Figure 2 Simulation Of Ann Of Our Approachmentioning
confidence: 99%
“…A chatbot is an automated computer program that fundamentally simulates human conversations such as the works of [1,2,3]. The evaluation of the chatbot's User Interface (UI) that was done for COVID-19 in [4] shows that the best approach is the interactive chatbot that can answer the user in conversational way and accept the free hand input, which depends on AI as this paper introduces. There is different architecture to classify text, and the word2vec embedding model [5] and GloVe [6] are embedding dictionaries, while a bag of the word (BoW) [7] and BoW TF-IDF [8] are vectorization methods that convert the textual data to numeric data in vectors shape.…”
Section: Introductionmentioning
confidence: 99%